Bioactive Metabolite Produced by Phomopsis sp., an Endophytic Fungus in Allamanda cathartica Linn. - J. Muthumary, K. Nithya, (Recent Research in Science and Technology, 2011)
Endophytes are microbial entities that live within living tissues of plants. In most cases their relationship with the host plant is symbiotic and probably mutualistic. Many are capable of synthesizing bio-active compounds that can be used by the plant for defense against fungi and bacteria. Some of these compounds have been proven useful for novel drug discovery. By encouraging the endophytes to grow outside the plant in nutrient rich media, it is possible to harvest the bio-active compounds that they produce. In the present investigation we are trying to isolate endophytic fungi from Allamanda cathartica (Apocynaceae). The secondary metabolite obtained from the endophytic fungi was found to inhibit the growth of human pathogenic bacteria. The compound was extracted with organic solvents and bioautogram was done to check compoundÃ¢â‚¬â„¢s antibacterial activity.Ã‚Â Thin layer chromatogram and various other spectroscopic analyses were done to identify the compound as terpene.